PENGARUH PERKARA DI PENGADILAN, KARAKTERISTIK DEWAN KOMISARIS, DAN PENGUNGKAPAN SECARA PROAKTIF TERHADAP KINERJA PERUSAHAAN LISTING BEI - Sulaiman Sulaiman; Nur Cahyonowati (Diponegoro Journal of Accounting, 2015)
In Indonesia, corporate governance is an important tool in achieving corporate goals. Many companies implement corporate governance ont he various aspects. This study aimed to examine the effect of corporate governance on various aspect; case on court , board size, number of independent commisioners, number of board meetings, number of other companies’ boards in which the commissioners are members ,  frequency of board meetings, disclosure of earnings forecasts, and disclosure of CSR on the performance of companies with  size as variable control   The population in this research are all companies in all areas of business listed on the Stock Exchange in 2013. The sampling method used in this research is cross-sectional sampling. The number of samples in this research are 307 companies.The results show that the disclosure of CSR has a significant effect on the performance of the company, while the other independent variables have no significant effect on the performance of the company.